GABAergic dysfunction, neural network hyperactivity and memory impairments in human aging and Alzheimer’s disease - Jiménez-Balado, Joan; Eich, Teal S. (Seminars in cell & developmental biology, 2021)
In this review, we focus on the potential role of the γ-aminobutyric acidergic (GABAergic) system in age-related episodic memory impairments in humans, with a particular focus on Alzheimer’s disease (AD). Well-established animal models have shown that GABA plays a central role in regulating and synchronizing neuronal signaling in the hippocampus, a brain area critical for episodic memory that undergoes early and significant morphologic and functional changes in the course of AD. Neuroimaging research in humans has documented hyperactivity in the hippocampus and losses of resting state functional connectivity in the Default Mode Network, a network that itself prominently includes the hippocampus—presaging episodic memory decline in individuals at-risk for AD. Apolipoprotein ε4, the highest genetic risk factor for AD, is associated with GABAergic dysfunction in animal models, and episodic memory impairments in humans. In combination, these findings suggest that GABA may be the linchpin in a complex system of factors that eventually leads to the principal clinical hallmark of AD: episodic memory loss. Here, we will review the current state of literature supporting this hypothesis. First, we will focus on the molecular and cellular basis of the GABAergic system and its role in memory and cognition. Next, we report the evidence of GABA dysregulations in AD and normal aging, both in animal models and human studies. Finally, we outline a model of GABAergic dysfunction based on the results of functional neuroimaging studies in humans, which have shown hippocampal hyperactivity to episodic memory tasks concurrent with and even preceding AD diagnosis, along with factors that may modulate this association. •Episodic memory loss is the principal clinical hallmark of Alzheimer’s disease (AD).•Hippocampal hyperactivity correlates with episodic memory failures in aging.•GABA synchronizes neuronal activity in the hippocampus.•GABA levels may be modulated by AD-risk factors.•The GABAergic system may link AD-risk factors and episodic memory decline.